Low band gap selenophene-diketopyrrolopyrrole polymers exhibiting high and balanced ambipolar performance in bottom-gate transistors - Shahid,M; McCarthy-Ward,T; Labram,J; Rossbauer,S; Domingo,EB; Watkins,SE; Stingelin,N; Anthopoulos,TD; Heeney,M (Chemical Science, 2012)
We report the synthesis of a selenophene-diketopyrrolopyrrole monomer and its co-polymerisation with selenophene and thieno[3,2-b]thiophene monomers by Stille coupling. The resulting low band gap polymers exhibit ambipolar charge transport in organic field effect transistors. High and balanced electron and hole mobilities in excess of 0.1 cm2 V-1 s-1 were observed in bottom-gate, bottom-contact devices, suggesting that selenophene inclusion is a promising strategy for the development of ambipolar organic semiconductors.